Cousinia khoiensis (Asteraceae, Cardueae), a new species from north-west of Iran - Attar, Farideh; Mirtadzadini, Mansour; Atazadeh, Neda (Mediterranean Botany, 2026)
A new endemic species (Asteraceae, Cardueae) is described as Cousinia khoiensis on the basis of specimens collected in West Azarbaijan Province, Iran. The distribution area of the new species belongs to the distribution range of the species of sect. Cousinia in the northwest of Iran. It is also morphologically similar to sect. Cousinia. These similarities are mainly in some characters such as the size and shape of the involucre, the number of flowers, the height of the plant and the texture of the leaves. The main differences between the new species and the members of sect. Cousinia in Iran are: the shape of the leaves, the number of phyllaries, the size of the capitula and the colour of the corolla. Cousinia khoiensis is compared with the closest species, including C. microcephala, C. sivasica, C. woronowii and C. calolepis. C. sivasica and C. woronowii of sect. Cousinia are distributed in Turkey, and C. calolepis belongs to sect. Stenocephalae. The holotype and isotype specimens of Cousinia khoiensis are illustrated, together with close-ups of various parts of the new species. An identification key for all taxa of sect. Cousinia in Iran as well as C. sivasica and C. woronowii, which is distributed in Turkey, has been provided. The number of species in the sect. Cousinia in Iran, including the new species, is 12. The relationship of Cousinia khoiensis and the related taxa was presented separately. In addition, a distribution map showing the distribution range of C. khoiensis and the related species is presented here.